Residual stress evaluation at the micrometer scale: Analysis of thin coatings by FIB milling and digital image correlation - Korsunsky, A; Sebastiani, M; Bemporad, E (2010)
In this report, an optimised method for residual stress determination at the microscopic scale is presented. The newly proposed approach involves incremental Focused Ion Beam (FIB) milling of annular trenches at material surface, combined with high resolution SEM imaging of a previously deposited marker pattern. Digital image correlation (DIC) analysis of the relative displacements between markers with respect to the undisturbed state provides a measure of strain relief. Results of finite element modeling show that the proposed configuration gives complete strain relief when the annular trench depth becomes comparable with the diameter of the remaining stub, thus allowing analytical calculation of the average residual stress from measured strain components. Basing on results of modeling, the experimental methodology has been developed and optimised for residual stress analysis in thin coatings. In order to cover a wide range of material properties and residual stress states, two different materials have been selected: TiN CAE-PVD coating (hard and stiff, with compressive residual stress) on WC-Co substrate, and also an Au MS-PVD coating (soft and compliant, with tensile residual stress). The procedure for the optimization of FIB milling parameters is reported. Results are validated by comparison with residual stress evaluation by X-ray diffraction and curvature measurement on the two different specifically selected PVD coatings. © 2010 Elsevier B.V.